Outcomes of and treatment planning considerations for a hybrid technique delivering proton pencil-beam scanning radiation to women with metal-containing tissue expanders undergoing post-mastectomy radiation. (November 2021) - DeCesaris, Cristina M.; Mossahebi, Sina; Jatczak, Jenna; Rao, Avani D.; Zhu, Mingyao; Mishra, Mark V.; Nichols, Elizabeth
Highlights: Details of technique, including beam angles, anatomic criteria, and image guidance. Descriptions of target coverage and doses to OARs, and acute toxicity profiles. Figures/images as visual guides for beam arrangements and expected dose distributions. Abstract: Background: Following mastectomy, immediate breast reconstruction often involves the use of temporary tissue expanders (TEs). TEs contain metallic ports (MPs), which complicate proton pencil-beam scanning (PBS) planning. A technique was implemented for delivering PBS post-mastectomy radiation (PMRT) to patients with TEs and MPs. Methods: A protocol utilizing a hybrid single- and multi-field optimization (SFO, MFO) technique was developed. Plans were robustly optimized using a Monte Carlo algorithm. A CTV_eval structure including chest wall (CW) and regional nodal (RNI) targets and excluding the TE was evaluated. Organ at risk (OAR) dosimetry and acute toxicities were analyzed. Results: Twenty-nine women were treated with this technique. A 2-field SFO technique was used superior and inferior to the MP, with a 3 or 4-field MFO technique used at the level of the MP. Virtual blocks were utilized so that beams did not travel through the MP. A port-to-CW distance of 1 cm was required. Patients underwent daily image-guidance to ensure the port remained within a 0.5 cm internal planning volume (ITV). Median RT dose to CTV_eval was 50.4 Gy (45.0–50.4). Median 95% CTV_eval coverage was 99.5% (95–100). Optically stimulated luminescent dosimeter (OSLD) readings were available for 8 patients and correlated to the dose measurements in the treatment planning system (TPS); median OSLD ratio was 0.99 (range, 0.93–1.02). Conclusions: Delivering PMRT with PBS for women with metal-containing TEs using a hybrid SFO/MFO technique is feasible, reproducible, and achieves excellent dose distributions. Specialized planning and image-guidance techniques are required to safely utilize this treatment in the clinic.